A Comparison Principle for the Mean Curvature Flow Equation with Discontinuous Coefficients - Cecilia De Zan; Pierpaolo Soravia (International Journal of Differential Equations)
We study the level set equation in a bounded domain when the velocity of the interface is given by the mean curvature plus a discontinuous velocity. We prove a comparison principle for the initial-boundary value problem whose consequence is uniqueness of continuous solutions and well- posedness of the level set method.